2021
DOI: 10.1002/adma.202008517
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap to Cardiac Tissue‐Engineered Construct Preservation: Insights from Cells, Tissues, and Organs

Abstract: Worldwide, over 26 million patients suffer from heart failure (HF). One strategy aspiring to prevent or even to reverse HF is based on the transplantation of cardiac tissue‐engineered (cTE) constructs. These patient‐specific constructs aim to closely resemble the native myocardium and, upon implantation on the diseased tissue, support and restore cardiac function, thereby preventing the development of HF. However, cTE constructs off‐the‐shelf availability in the clinical arena critically depends on the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Moreover, heart transplants and left ventricular assist devices are limited by supply shortages and related complications caused by infection, bleeding, stroke, and right ventricular failure, respectively. [ 145 ] Therefore, during the past 40 years, many efforts have been invested in the study of the prospects of stem cells for HF treatment. Unfortunately, the body of evidence accumulated so far has shown that stem cell therapy does not produce clinically meaningful therapeutic effects for HF owing to poor control, poor retention in the infarct area, and the low survival rate of the cells injected into the patient.…”
Section: Heart Failure Therapymentioning
confidence: 99%
“…Moreover, heart transplants and left ventricular assist devices are limited by supply shortages and related complications caused by infection, bleeding, stroke, and right ventricular failure, respectively. [ 145 ] Therefore, during the past 40 years, many efforts have been invested in the study of the prospects of stem cells for HF treatment. Unfortunately, the body of evidence accumulated so far has shown that stem cell therapy does not produce clinically meaningful therapeutic effects for HF owing to poor control, poor retention in the infarct area, and the low survival rate of the cells injected into the patient.…”
Section: Heart Failure Therapymentioning
confidence: 99%
“…The iPSC techniques also eliminate the ethical issues surrounding the use of embryonic stem cells [74,75]. Taking this one step further, recent advances in tissue engineering have allowed for the design and construction of hiPSC-cardiomyocyte-based cardiac tissue-engineered constructs with a variety of therapeutic implications [76,77].…”
Section: Disease-in-a-dishmentioning
confidence: 99%
“…Despite the promise of cTE, the field currently faces challenges, including a lack of maturation of the implanted cellsthat promote potential arrhythmiasa needed human leukocyte antigen (HLA) match to prevent rejection of the graft, and the time required for cTE production. [20][21][22] A very practical and logistic problem to date, is a lack of preservation methods that will allow transport between production sites and hospitals to facilitate cTE construct application in different environments and further scalability and commercialization of cTE constructs. These challenges are somewhat comparable to those faced by heart transplantation, which has been partially overcome by ex vivo organ preservation methods (up to a maximum of eight hours), ultimately increasing the number of available donor hearts by 15-30%.…”
Section: Introductionmentioning
confidence: 99%